Phytoplankton quantity as an indicator of eutrophication in Finnish coastal waters : applications within the Water Framework Directive - Kauppila, Pirkko (Finnish Environment Institute, 2013)
The tackling of coastal eutrophication requires water protection measures based on status assessments of water quality. The main purpose of this thesis was to evaluate whether it is possible both scientifically and within the terms of the European Union Water Framework Directive (WFD) to assess the status of coastal marine waters reliably by using phytoplankton biomass (ww) and chlorophyll a (Chl) as indicators of eutrophication in Finnish coastal waters. Empirical approaches were used to study whether the criteria, established for determining an indicator, are fulfilled.The first criterion (i) was that an indicator should respond to anthropogenic stresses in a predictable manner and has low variability in its response. Summertime Chl could be predicted accurately by nutrient concentrations, but not from the external annual loads alone, because of the rapid affect of primary production and sedimentation close to the loading sources in summer. The most accurate predictions were achieved in the Archipelago Sea, where total phosphorus (TP) and total nitrogen (TN) alone accounted for 87% and 78% of the variation in Chl, respectively. In river estuaries, the TP mass-balance regression model predicted Chl most accurate when nutrients originated from point-sources, whereas land-use regression models were most accurately in cases when nutrients originated mainly from diffuse sources. The inclusion of morphometry (e.g. mean depth) into nutrient models improved accuracy of the predictions.The second criterion (ii) was associated with the WFD. It requires that an indicator should have type-specific reference conditions, which are defined as “conditions where the values of the biological quality elements are at high ecological status”. In establishing reference conditions, the empirical approach could only be used in the outer coastal waters types, where historical observations of Secchi depth of the early 1900s are available. Most accurate prediction was achieved in the Quark. However, the average reference values in the ...